Gallstone ileus an uncommon cause of bowel obstruction - Zarco Arreola, Karla I.; Yañez Herrera, Guadalupe G. (International Journal of Research in Medical Sciences, 2022)
Gallstone ileus is caused by the impaction of one or more gallstones within the gastrointestinal tract leading to mechanical obstruction. Thomas Bartholin described the first case in 1654 during an autopsy. This manuscript describes a case of gallstone ileus in a 39-year-old woman who presented data of intestinal occlusion and hemodynamic instability, being managed with intestinal resection for a 7 cm stone and entero-entero anastomosis, achieving an adequate post-surgical evolution. It is a rare complication of cholelithiasis and is found in 2 to 3% of all cases associated with recurrent episodes of cholecystitis, it occurs predominantly in women. In elderly patients (>65 years) it accounts for 25% of all cases of small bowel obstruction and carries a fivefold increased risk of morbidity (20 to 57%) compared to other causes of small bowel obstruction.